Using of Electronic Marketing Channels in Building Customer Loyalty in Hotels - Saeed, Ahmed Ahmed Abdel Salam; Arous, Saleh Abd El Hamid; Ahmed, Gihan Nabil (جامعة مدينة السادات - كلية السياحة والفنادق, 2018)
يعد التسويق الإلكتروني من أحدث الأدوات الحديثة في عالم التسويق، حيث يشير إلى استخدام وسائل الإعلام الرقمية والإنترنت للمساعدة في بيع المنتجات أو الخدمات وبناء علاقات مع العملاء الحاليين والمحتملين وبالتالي أصبحت الحاجة إليه ضرورية وملحة وحيوية خاصة في الفنادق من أجل البقاء والمنافسة. هدفت الدراسة إلي التعرف علي قنوات التسويق الإلكتروني في الفنادق ومدي فعاليته في بناء ولاء العملاء في صناعة الفنادق ومدي فعالية زيادة الإشارات للدخول علي مواقع الفنادق المصرية واستخدام تلك الفنادق للموبايل كقناة تسويق إلكتروني ولقد توصل البحث إلى توضيح التأثير الإيجابي للبريد الإلكتروني المرسل من الفنادق المصرية علي بناء علاقات جيدة مع العملاء وتعزيز الثقة بالإضافة إلي أن لمواقع التواصل الاجتماعي (فيس بوك - تويتر - يوتيوب - جوجل بلس) تأثير علي خلق مناخ من الثقة في العلامة التجارية للفنادق مما ترتب عليه ضرورة اهتمام الفنادق بتطوير وتحسين المواقع الإلكترونية لها والتركيز على استخدام البريد الإلكتروني بشكل فعال لضمان التواصل مع العملاء.
As the lodging sector evolves into a more technology-oriented industry, the need to understand electronic marketing practices becomes more important for marketing strategies. The main purpose of this study is to understand the ability of Egyptian hotels to adopt electronic marketing strategies as vital marketing tools in marketing management, and discuss the benefits and challenges facing decision makers at five star Egyptian hotels. A field study was conducted with customers in 23 five star hotels in Cairo, Hurghada and Sharm El Sheikh. The collected data have been classified and tabulated to be thoroughly analyzed through computer software. The researcher has calculated the necessary percentages and formed the required repetitive tables to satisfy one of the most important descriptive statistical techniques in identifying and defining the research variables and their repetition rates within the drawn sample. The results indicated that customer is not satisfied with Egyptian electronic marketing content, Egyptian hoteliers are aware of the importance of electronic marketing and its effect on building customer loyalty. This study recommended that hoteliers have to increase the electronic marketing budget and use new communication and distribution technology to encourage customers to the Internet.
Keywords: التسويق الإلكتروني -- الفنادق السياحية -- رضا العملاء -- العلامات التجارية -- مواقع التواصل الإجتماعى -- مصر